Augmented Nested Arrays With Enhanced DOF and Reduced Mutual Coupling - Liu, Jianyan; Zhang, Yanmei; Lu, Yilong; Ren, Shiwei; Cao, Shan (IEEE transactions on signal processing, 2017)
Recently, nonuniform linear arrays (e.g., coprime/nested array) have attracted great attention of researchers in array signal processing field due to its ability to generate virtual difference coarrays. In the array design, a critical problem is where to place the sensors for optimal performance aiming for a maximum degree of freedom capacity and a minimum mutual coupling ratio, simultaneously. An augmented nested array concept is proposed by splitting the dense subarray of nested array into several parts, which can be rearranged at the two sides of the sparse subarray of nested array. Specifically, four closed-form expressions for the physical sensor locations and the virtual sensor locations are derived for any given element number. Compared to the (super) nested array having the same element number, the newly formed augmented nested array possesses higher degree-of-freedom capacity and less mutual coupling. In the end, numerical simulation results validate the effectiveness of the proposed arrays.